Navigating the Crossroads: Democracy, National Identity and Memory Politics in Eastern Europe and Russia - Hautaniemi, Tiia (My University, 2024)
In the early 21st century, democracy encountered challenges around the world, without yet reaching a level of global crisis. Recently, however, established democracies have seen a rise in intolerance and right-wing populism, with the phenomenon of democratic backsliding becoming a significant concern, particularly within the European Union. Efforts to promote democracy have been hindered by both domestic challenges and external influences from authoritarian states. This paper, conducted as part of a workshop on the future of jurisprudence, employs a social sciences case study method to explore current democratic challenges and the role of memory politics in Eastern Europe and Russia. It addresses three interconnected themes: the challenges facing democracy, self-perception of contemporary Russia as a great power and the use of memory politics in Eastern Europe and Russia to advance political agendas. The paper concludes that memory politics and memory laws exert considerable influence in shaping historical interpretations, often prioritising national memories and ideological viewpoints. Accordingly, memory politics and laws have intensified state tensions, both within the European Union and between Central and Eastern Europe and Russia. An examination of self-perception of contemporary Russia as a great power reveals a complex national identity shaped by history and a narrative of greatness. Its advocacy for a multipolar world order signifies an aspiration to affirm sovereignty and mitigate Western hegemony, despite current strained relations with the West.

2000-luvun alussa demokratia kohtasi maailmanlaajuisesti monia haasteita, ajautumatta kuitenkaan vielä globaalin kriisin tasolle. Viime aikoina vakiintuneissa demokratioissa suvaitsemattomuus sekä oikeistopopulismi ovat kuitenkin olleet nousussa, ja demokratialuisu ilmiönä on noussut keskeiseksi huolenaiheeksi erityisesti Euroopan unionissa. Demokratian edistämistä ovat vaikeuttaneet sekä kansalliset että ulkoiset, autoritaarisista valtioista, johtuvat haasteet. Tämä opinnäytetyö on tehty osana tulevaisuuden juridiikkaa tutkivaa “Kestävä kehitys ja oikeusvaltio” - työpajaa. Nykyisiä demokratian haasteita ja muistin politiikan roolia Itä-Euroopassa ja Venäjällä on tässä työssä tutkittu soveltamalla yhteiskuntatieteiden tapaustutkimusmenetelmää. Opinnäytetyössä tarkastellaan kolmea, toisiinsa kytkeytyvää teemaa: demokratian kohtaamia haasteita, nyky-Venäjän käsitystä suurvalta asemastaan sekä muistin politiikan hyödyntämistä poliittisen agendan tukemisessa Itä-Euroopassa ja Venäjällä. Tutkielman lopputulemana on, että muistin politiikalla ja muistilaeilla on huomattava vaikutus historiaa koskevien tulkintojen muokkaamisessa. Etusijalle asetetaan monesti oma kansallinen muisti ja ideologia. Tästä johtuen muistin politiikka ja -lait ovat lisänneet valtioiden välisiä jännitteitä paitsi Euroopan unionin sisällä, myös Keski- ja Itä-Euroopan ja Venäjän välillä. Nyky-Venäjän käsitys suurvaltastatuksestaan tuo esiin monitahoisen kansallisen identiteetin, joka on muotoutunut pitkälti historiaa ja suuruutta korostavan narratiivin kautta. Venäjän tavoittelema moninapainen maailmanjärjestys kuvastaa sen pyrkimyksiä vahvistaa suvereniteettiaan ja vähentää länsimaista hegemoniaa, haastavista länsisuhteistaan huolimatta.
Keywords: democratic backsliding, memory politics, memory laws, national identity, Russia, demokratialuisu, muistin politiikka, muistilait, kansallisidentiteetti, Venäjä